Time-to-Detection in Culture Predicts Risk of Mycobacterium tuberculosis Transmission: A Cohort Study. (11th April 2014) - O'Shea, Matthew K.; Koh, Gavin C. K. W.; Munang, Melinda; Smith, Grace; Banerjee, Arpan; Dedicoat, Martin
Abstract : Time to detection (TTD) of Mycobacterium tuberculosis in liquid culture of spontaneously produced sputum samples can be used to identify patients at high risk of transmitting tuberculosis. A simple system of grading chest radiographs (from 0 to 6) correlates well with TTD. Abstract : Background.  Contact screening is an essential component of all tuberculosis control strategies. We hypothesize that time-to-detection (TTD) in liquid culture of spontaneously produced sputum samples may help identify index cases at high risk of transmission. Methods.  We studied retrospectively a cohort of patients with pulmonary tuberculosis in Birmingham, United Kingdom (January 2010–December 2012). We studied the correlation of TTD with the risk of transmission of infection from index cases to contacts and compared this with sputum microscopy. Chest radiographs (CXRs) were graded from 0 to 6 (0, no radiographic evidence of disease; 5, bilateral cavitation; and 6, miliary disease). Results.  Of the 184 cases of pulmonary tuberculosis reported during the study period, 111 were included in the final study, and these generated 825 contacts. A transmission event (new latent or active tuberculosis) was identified in 165 contacts (transmission rate 0.20). Short TTD (<9 days) was associated with an increased risk of transmission (odds ratio, 2.56; P < .001), and this relationship persisted after adjusting for potential confounders. A 1-point increase in CXR grade correlated with a 3.2-day decrease in TTD ( P < .001), and this correlation persisted after adjustment for potential confounders. Conclusions.  TTD < 9 days identifies patients at high risk of transmitting tuberculosis and is superior to sputum smear. CXR grade at diagnosis predicts patients with short TTD. Our findings have the potential to guide the organization and prioritization of contact investigations in similar settings.